CD4+ Recent Thymic Emigrants Are Recruited into Granulomas during Leishmania donovani Infection but Have Limited Capacity for Cytokine Production. - John W J Moore; Lynette Beattie; Mohamed Osman; Benjamin M J Owens; Najmeeyah Brown; Jane E Dalton; Asher Maroof; Paul M Kaye (PLoS ONE)
Recent thymic emigrants (RTEs) represent a source of antigen-naïve T cells that enter the periphery throughout life. However, whether RTEs contribute to the control of chronic parasitic infection and how their potential might be harnessed by therapeutic intervention is currently unclear. Here, we show that CD4+ recent thymic emigrants emerging into the periphery of mice with ongoing Leishmania donovani infection undergo partial activation and are recruited to sites of granulomatous inflammation. However, CD4+ RTEs displayed severely restricted differentiation either into IFNγ+ or IFNγ+TNFα+ effectors, or into IL-10-producing regulatory T cells. Effector cell differentiation in the chronically infected host was not promoted by adoptive transfer of activated dendritic cells or by allowing extended periods of post-thymic differentiation in the periphery. Nevertheless, CD4+ RTEs from infected mice retained the capacity to transfer protection into lymphopenic RAG2-/- mice. Taken together, our data indicate that RTEs emerging into a chronically inflamed environment are not recruited into the effector pool, but retain the capacity for subsequent differentiation into host protective T cells when placed in a disease-free environment.